Estudos de efeitos de spin em diodos de tunelamento ressonante do tipo-p - Bezerra, Anibal Thiago (Universidade Federal de São Carlos, 2010)
The aim of this work was to complement the studies of the mechanisms of control of the degree of circular polarization of emission from resonant tunneling diodes p-type (RTD) by analyzing the optical properties and transport of this type of structure. We focus primarily on the influence of the width of quantum well to these properties and the possible injection of spin-polarized charge carriers, from the two-dimensional hole gas formed in the accumulation layer adjacent to the barriers. First, we discuss the theoretical foundations necessary for understanding the work, followed by the description of samples and experimental methods to perform this study. The results showed that the degree of circular polarization of luminescence of the quantum well is strongly correlated with the transport across the diode and with the separation of the emission energy of each spin component. We note also that reversal signal degree of polarization in the regions of resonant tunneling, which were associated with different Landè g-factors of electrons and holes and the injection through the spin channels. Regarding the issue of contacts emition, we observed the presence of two major contributions, one related to the three-dimensional contact and other related two-dimensional hole gas formed in the accumulation layer. The luminescence of gas did not show significant spin polarization, preventing direct analysis of its influence on the spin properties of quantum well. Finally, we conclude that the variation in width of the quantum well can greatly influence the spin properties of RTDs, and the study of these properties may allow the architecture of new spintronic devices.
Keywords: Física do estado sólido; Spintronics; Diodos; Fotoluminescência; Transporte eletrônico; CIENCIAS EXATAS E DA TERRA::FISICA